In vitro Biological Activities and Fatty Acid Composition Analysis of Musa paradisiaca L. Inflorescence (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Musa paradisiaca L. is native to tropical climate. Inflorescences of this herb are used as a treatment of digestive distresses. This study involved analysis of the fatty acid contents and some in-vitro pharmacological activities of the inflorescence. Modified Kupchan method was used for extraction in solvents of varying polarity. Fatty acid content analysis was conducted on n-hexane extract; Palmitoleic acid was found to be the highest in proportion in both bound (34.40%) and free (37.80%) forms. n-hexane and dichloromethane extracts exhibited cytotoxicity against carcinoma cell (HeLa cell line). Ethyl acetate extract possessed significant amount of free radical (DPPH) scavenging capability (IC50 = 66.92±0.3065 μg/ml). The n-Hexane extract was found to be rich in phenolics (26.40 ± 0.033 mg GE/g) and flavonoids (83.40± 0.099 mg QE/g). Dichloromethane fraction exhibited the highest zone of inhibition (15 mm) against the bacterium Shigella dysenteriae. Ethyl acetate fraction showed blood clot lysis activity of 29.35% (standard streptokinase 63.05%). Presence of potent bioactivities imply the prospects of this sample as a source of lead compounds for effective formulations against chronic digestive diseases.Dhaka Univ. J. Pharm. Sci. 23(1): 69-76, 2024 (June)